Critical Success Factors and Challenges in Applying Agile Project Management: A Systematic Literature Review - Setiawan, R. Hendy; Sakapurnama, Eko (International Journal of Science and Society, 2025)
Agile project management has gained wide adoption for managing complex, dynamic projects, yet its success depends on various enabling factors. Despite its popularity, organizations frequently encounter challenges in implementing Agile practices successfully. This study systematically reviews existing literature to identify and synthesize the critical success factors (CSFs) that facilitate Agile project effectiveness, while simultaneously examining the prevalent obstacles organizations face during Agile adoption. Results indicate that Agile project success is largely facilitated by executive support, effective teamwork, active customer involvement, clear communication, and disciplined Agile execution. Conversely, significant barriers identified include organizational resistance, inadequate training, limited understanding of Agile principles, and coordination complexities in scaled or hybrid implementations. Successful Agile adoption necessitates balancing these enabling factors while proactively addressing prevalent challenges through robust leadership, comprehensive training, and tailored implementation strategies. Future research should explore longitudinal impacts, detailed failure analyses, and implications of emerging technologies on Agile effectiveness.